Handbook of Research on ICTs and Management Systems for Improving Efficiency in Healthcare and Social Care 2013
DOI: 10.4018/978-1-4666-3990-4.ch006
|View full text |Cite
|
Sign up to set email alerts
|

New Telerehabilitation Services for the Elderly

Abstract: The world’s population is getting older with the percentage of people over 60 increasing more rapidly than any other age group. Telerehabilitation may help minimise the pressure this puts on the traditional healthcare system, but recent studies showed ease of use, usability, and accessibility as unsolved problems, especially for older people who may have little experience or confidence in using technology. Current migration towards multimodal interaction has benefits for seniors, allowing hearing and vision pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In addition, recent studies showed that ease of use, usability, and accessibility for telerehabilitation services could be sometimes unsolved problems, especially for older people and people who live in rural areas who may have little experience or confidence in using advanced technology. 27 There is a significant need for occupational therapists to document, research, and publish on the efficacy and effectiveness of clinical services provided using telehealth and telerehabilitation technologies. Telerehabilitation research needs larger and more comprehensive analyses of patient outcomes and a variety of clinical outcome measures used in telerehabilitation are needed.…”
Section: Barriers/limitations and Solutions/future Recommendationsmentioning
confidence: 99%
“…In addition, recent studies showed that ease of use, usability, and accessibility for telerehabilitation services could be sometimes unsolved problems, especially for older people and people who live in rural areas who may have little experience or confidence in using advanced technology. 27 There is a significant need for occupational therapists to document, research, and publish on the efficacy and effectiveness of clinical services provided using telehealth and telerehabilitation technologies. Telerehabilitation research needs larger and more comprehensive analyses of patient outcomes and a variety of clinical outcome measures used in telerehabilitation are needed.…”
Section: Barriers/limitations and Solutions/future Recommendationsmentioning
confidence: 99%
“…The evaluation methodology described was first used to evaluate the Tele-Rehabilitation service under development in the LUL project [14]. This session presents the prototype test results as an example of the methodology application.…”
Section: Results From a Case Studymentioning
confidence: 99%
“…This session presents the prototype test results as an example of the methodology application. In general terms, this service allows supervised remote exercise sessions as a way to maintain health and prevent illness [14]. Table 1 profiles the facilitators and barriers mentioned by the clients and Table 2 those mentioned by the service provider.…”
Section: Results From a Case Studymentioning
confidence: 99%
“…This application allows the execution of rehabilitation services to remote and possible underserved populations, which can improve overall quality of life and prevent secondary complications [15]. This application consists on two modules, one for the user at home and another for a health professional at a remote location.…”
Section: A Concrete Scenario Of Applica-tionmentioning
confidence: 99%